Photofunctionalized Europium(III) complexes with circularly polarized luminescence - Md. Jahidul Islam, PhD; Naima Sharmin (Chemical Physics Impact)
Europium(III) complexes that emit circularly polarized light (CPL) have potential applications in various fields, including bioimaging, sensing, and optoelectronic devices. This study investigates the synthesis and characterization of europium(III) complexes having CPL activity by incorporating chiral ligand (+)-3-(trifluoroacetyl)camphor (tfc) and triphenylene diphenylphosphine oxide (DPO) ligands . The europium acetate salt was converted to europium trifluoroacetyl camphorate ([Eu(tfc)3)(H2O)]) in the 1st step of the four-step synthesis reaction. In the 2nd step chlorodiphenylphosphine and 6-bromotriphenylene in the presence of the catalyst n-BuLi at -80 °C in dry THF solvent produce triphenylene phosphine ligand. In the 3rd step of the synthesis process, the synthesized triphenylene diphenyl phosphine undergoes oxidation to phosphine oxide, DPO using hydrogen peroxide (H2O2) as a catalyst at a low temperature of 0 °C. In the final and fourth step of the chiro optical europium complex synthesis, [Eu(tfc)3(DPO)2](H2O)2 was prepared by reacting the previously synthesized DPO ligand with [Eu(tfc)3](H2O)2 in dichloromethane solvent at room temperature for a duration of three hours. The NMR, FTIR, Elemental analysis, TGA and powder XRD confirmed the proposed molecular formula C66H70F9O6EuP. Upon excitation at 375 nm, the complex displayed characteristic sharp emission peaks in the visible region emission bands which were observed at 580, 595, 614, 652, and 703 nm, corresponding to the 4f-4f transitions of the Eu(III) ion. The high intensity ratio of 5D0–7F2 to 5D0–7F1 indicated a non-centrosymmetric ligand arrangement. The synthesized complex displayed significant circularly polarized luminescence (CPL) properties, exhibiting an absolute gCPL value of 0.025 and an absolute quantum yield of 4.09 %. With a 8 % sensitization efficiency and a 0.56 ms photoluminescent lifetime, this complex shows promise for potential applications in optoelectronic devices and chiral sensing. The challenges such as back energy transfer and structural stability limited the overall luminescence efficiency.